IMPLEMENTASI TIME DRIVEN ACTIVITY BASED COSTING (TDABC) PADA USAHA KECIL MENENGAH (UKM) TAPE HANDAYANI 82 BONDOWOSO - Deni Oktavia (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2013)
Firms need to assess the competitive advantage by determining the strategic advantages. TDABC is an instrument to achieve operational improvements in practice, reducing non value added activities and merge similar activities into one place. The objectives of this research is to calculate using the time driven activity based costing ( TDABC ) method on Tape Handayani 82 Small and Medium Enterprises ( SMEs ) in Bondowoso Regency. This study is a qualitative research. Design of qualitative methods is general, flexible, and thrives in the process of research. Researchers involve directly in order obtaining as much information. One focus of qualitative research is a phenomenon that can only be explained and cannot be measured, and the phenomenon observed by researchers in the field. Object of study is the Tape Handayani 82 SME that engaged in tape industry. Selections of the research object because tape is typical of the Bondowoso. Tape has relatively high market share, but in efficiency of time management, activities undertaken, not in accordance with time -driven activity-based costing concepts. Data collection methods used in this qualitative approach. This step is done by directly observe and conduct interviews with employer and owner who do day-to- day business activities especially financial. Recognition of cost of tape products show too low. As for the fuel smoked tape, tape, dodol and suwar suwir show the company recognize higher. Calculations with TDABC provide more accurate information related to the consumption cost. The result can be used to revise cost product. Added analysis of the activities does by identifying, preparing and evaluating activities description. The analysis identifies what activities are done, how many people who carry out these activities, the time and resources necessary to do the activity. TDABC analysis indicates that Tape 82 Handayani is not efficient yet. 70 % is still idle capacity so it is necessary to create added value activity. Idle capacity led to increased costs or consumes resources costs that are not necessary. Keywords: TDABC, activity, poduct cost, tape